The effectiveness of the STOP-X training program on the knee valgus angle and balance in female basketball players with dynamic knee valgus: a randomized controlled trial (BMC Sports Science, Medicine and Rehabilitation, 2024)
Background Dynamic knee valgus (DKV) accompanied by poor balance is the cause of anterior cruciate ligament (ACL) injury in athletes, and the identification and correction of these factors are always of interest to researchers. Therefore, the purpose of this research was to investigate the effect of the STOP-X program on the knee valgus angle and static and dynamic balance in female basketball players with DKV defects.